2023
DOI: 10.3389/fcvm.2023.1195464
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic insights into heat shock protein 27, a potential therapeutic target for cardiovascular diseases

Abstract: Heat shock protein 27 (HSP27) is a small chaperone protein that is overexpressed in a variety of cellular stress states. It is involved in regulating proteostasis and protecting cells from multiple sources of stress injury by stabilizing protein conformation and promoting the refolding of misfolded proteins. Previous studies have confirmed that HSP27 is involved in the development of cardiovascular diseases and plays an important regulatory role in this process. Herein, we comprehensively and systematically su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 127 publications
0
1
0
Order By: Relevance
“…HSPB1, HSPB4, and HSPB5 are essential for maintaining the balance of proteins in the eye, and abnormalities in their function are associated with ocular diseases such as cataract [199,200]. Moreover, studies have shown that HSPB1 is involved in the development of cardiovascular diseases by affecting apoptosis, autophagy, oxidative stress, and inflammatory responses [17,201]. The mechanisms through which mutant sHSPs cause disease are complex.…”
Section: Shsps and Diseasementioning
confidence: 99%
“…HSPB1, HSPB4, and HSPB5 are essential for maintaining the balance of proteins in the eye, and abnormalities in their function are associated with ocular diseases such as cataract [199,200]. Moreover, studies have shown that HSPB1 is involved in the development of cardiovascular diseases by affecting apoptosis, autophagy, oxidative stress, and inflammatory responses [17,201]. The mechanisms through which mutant sHSPs cause disease are complex.…”
Section: Shsps and Diseasementioning
confidence: 99%
“…HSPs are molecular chaperones that maintain protein stability, facilitate transport, and transmit signals within cells [26][27][28]. HSPs also play a crucial role in protecting cells from stress and preventing the degradation of severely damaged proteins [29,30].…”
Section: Cotreatment With Lr and 43 • C Hyperthermia Suppresses Ht-in...mentioning
confidence: 99%
“…The RECAST trial demonstrated increased levels of Heat Shock Protein 27 (HSP-27) following RIC [29]. Heat shock protein 27 has been shown to protect against ischaemic injury in pre-clinical models of cardiovascular disease [37]. There is evidence that RIC either reduces or attenuates the rise of S100β in ischaemic stroke [28,29].…”
Section: Introductionmentioning
confidence: 99%